AGN disks harden the mass distribution of stellar-mass binary black hole mergers - Yang, Y; Bartos, I; Haiman, Z; Kocsis, B; Márka, Z; Stone, NC; Márka, S (IOP Publishing, 2019)
The growing number of stellar-mass binary black hole mergers discovered by Advanced LIGO and Advanced Virgo are starting to constrain the binaries' origin and environment. However, we still lack sufficiently accurate modeling of binary formation channels to obtain strong constraints, or to identify subpopulations. One promising formation mechanism that could result in different black hole properties is binaries merging within the accretion disks of active galactic nuclei (AGNs). Here we show that the black holes' orbital alignment with the AGN disks preferentially selects heavier black holes. We carry out Monte Carlo simulations of orbital alignment with AGN disks, and find that AGNs harden the initial black hole mass function. Assuming an initial power-law mass distribution ${M}_{bh}^{-β }$, we find that the power-law index changes by Δβ ~ 1.3, resulting in a more top-heavy population of merging black holes. This change is independent of the mass of, and accretion rate onto, the supermassive black hole in the center of the AGN. Our simulations predict an AGN-assisted merger rate of ~4 Gpc−3 yr−1. With its hardened mass spectra, the AGN channel could be responsible for 10%–50% of gravitational-wave detections.